Three-dimensional chromosome architecture and drug addiction. (December 2019) - Chitaman, Javed M; Fraser, Peter; Feng, Jian
Highlights: Three-dimensional (3D) chromosome architecture is highly organized. 3D chromosome organization plays important roles in basic brain function. Altered 3D interactions are associated with neuropsychiatric disorders. Cocaine disrupts a particular DNA loop formation in the brain. Abstract : Aberrant gene expression underlies drug addiction. Therefore, studying the regulation of gene expression in drug addiction may provide mechanistic insights into this disease, for which there are still only limited treatments. Recently, the three-dimensional (3D) organization of linear DNA in the nucleus has been recognized as having a major influence on gene transcription. Here, we review its roles in both basic brain function and neuropsychiatric disorders, while also highlighting its emerging implications in drug addiction. Unraveling the 3D architecture of chromosomes in drug addiction is adding to our understanding of this disease and has the potential to trigger novel approaches for better diagnosis and therapy.